USD EXCHANGE RATE CHANGES AND COAL PRICE FLUCTUATIONS: IMPACT ON INDONESIAN COAL EXPORTS - Widati, Sekar Tri; Iranto, Dicky; Wiralaga, Harya Kuncara (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
Coal exports represent a significant component of the Indonesian economy, contributing to the country's foreign exchange earnings. In the context of globalization and international trade, Indonesia's coal export volume is influenced by a range of external factors, including exchange rates and coal prices in the international market. This study aims to determine the effect of exchange rates and international coal prices on Indonesia's coal export volume. This study employs time series data from 1992 to 2022 and the Error Correction Model (ECM) analysis method, utilizing the EViews 12 software, to examine the long-term and short-term relationships between the exchange rate and international coal prices and the volume of Indonesian coal exports. The results of the analysis indicate that in the short term, exchange rates and international coal prices do not exert a significant influence on the volume of Indonesian coal exports. Nevertheless, in the long term, the exchange rate and international coal prices exert a significant influence on the volume of Indonesian coal exports.